Life-threatening hemoptysis following mitral valvuloplasty for rheumatic mitral stenosis. (2019) - Sutherland, Mark E.; Haji, Hassan; Borgan, Saif M.; Eimer, Kelli M.; Reed, Robert M.; McCurdy, Michael T.
Abstract: Background: Massive hemoptysis is a rare complication of rheumatic mitral valve stenosis. Its recurrence following successful initial treatment of the stenosis has not, to our knowledge, been described. Case report: We describe a 58-year-old African American woman with a history of balloon valvuloplasty for the treatment of severe rheumatic mitral valve stenosis who presented to our institution with massive life-threatening hemoptysis due to recurrent mitral valve stenosis. Repeat balloon valvuloplasty was complicated postoperatively by severe mitral regurgitation and the patient expired from refractory cardiopulmonary collapse not amenable to further intervention. Conclusion: Life-threatening hemoptysis is a medical emergency requiring rapid source identification and treatment of the underlying etiology. A high degree of suspicion should be maintained for recurrence of mitral valve stenosis in patients presenting with life-threatening hemoptysis and risk factors of rheumatic heart disease, regardless of previous surgical management or unilateral chest x-ray signs.